Discovery and synthesis of tetrahydropyrimidinedione-4-carboxamides as endothelial lipase inhibitors. Issue 23 (15th December 2018) - Hu, Carol H.; Wang, Tammy C.; Qiao, Jennifer X.; Haque, Lauren; Chen, Alice Y.A.; Taylor, David S.; Ying, Xiaohong; Onorato, Joelle M.; Galella, Michael; Shen, Hong; Huang, Christine S.; Toussaint, Nathalie; et al.
Graphical abstract: Highlights: A series of tetrahydropyrimidinedione EL inhibitors was identified. New compounds showed measurable EL inhibition in human serum. Optimization led to4a with micromolar human serum potency and3g with acceptable mouse PK. Abstract: Endothelial lipase (EL) inhibitors have been shown to elevate HDL-C levels in pre-clinical murine models and have potential benefit in prevention and treatment of cardiovascular diseases. Modification of the 1-ethyl-3-hydroxy-1, 5-dihydro-2 H -pyrrol-2-one (DHP) lead, 1, led to the discovery of a series of potent tetrahydropyrimidinedione (THP) EL inhibitors. Synthesis and SAR studies including modification of the amide group, together with changes on the pyrimidinone core led to a series of arylcycloalkyl, indanyl, and tetralinyl substituted 5-amino or 5-hydroxypyrimidinedione-4-carboxamides. Several compounds were advanced to PK evaluation. Among them, compound4a was one of the most potent with measurable ELHDL hSerum potency and compound3g demonstrated the best overall pharmacokinetic parameters.